A critical analysis of the role of coltan in the Eastern region of the Democratic Republic of Congo's second war (1998-2003) - Moleko, Teboho Banele (Rhodes University, Faculty of Humanities, Department of Political and International Studies, 2015)
The role of natural resources in African conflicts has been subject to extensive scholarly analysis. However, much of this analysis has taken a narrow economic reductionist bias. As such, it is imperative that the dominant assumptions and accepted concepts and theories about the role of natural resources in African conflicts be re-examined. The aim of this thesis is to offer a revaluation of the role of coltan during the Democratic Republic of Congo's (DRC) Second War (1998-2003) through a critical engagement with the resource wars literature. The purpose is to offer a re-reading of the role of coltan in the DRC Second War and the broader regional and global economic context in which this conflict took place. It rejects the commonly cited assumption that the presence of coltan in the DRC means it is an initiator of conflict. Rather, this thesis argues that the central role of coltan in the DRC Second War was as an aggravator of conflict in that its exploitation was used by different parties to fund their military and political ambitions. This thesis also argues that the DRC's weak state structures and pivotal role within the Great Lakes region, as well as the international trade of coltan and the nature of the DRC coltan mining industry are all key factors in understanding coltan exploitation in the country's Eastern Region during the Second War.
Keywords: Congo (Democratic Republic) -- History -- 1997-; Natural resources -- Congo (Democratic Republic); Tantalite -- Congo (Democratic Republic); Natural resources -- Political aspects -- Congo (Democratic Republic); Power (Social sciences) -- Congo (Democratic Republic); Mines and mineral resources -- Congo (Democratic Republic)